Evaluation of the Program of Professional Education (PEP): The case of Minas Gerais, a State of Brazil - Tarrara Alves Horsth; Wesley de Almeida Mendes; Fernanda Gabriela Gandra Pimenta Magalhães; Bruno Silva Olher (Arizona State University, 2018)
The inclusion of young people and adults in the job market is a problem in developing countries, which requires the attention of the State that, through public educational policies, can help human and economic development. In support of these improvements, the Brazilian State created the Professional Education Program (PEP) to facilitate the access of young people and adults to technical vocational courses so they can better prepare themselves for the job market. Thus, the objective of this article is to verify whether the PEP has influenced or not influenced the access of young people to the job market in Minas Gerais, understanding this as one of the axes of human development. In order to achieve the proposed objective, documentary analyzes were carried out on the public policy in question, as well as statistical tests that verified the variations in the indexes of youth employability. It is concluded that this program was crucial for the improvement of the environment in question, and although not the only factor, but still an important program for the population of this state.